Mutation tracking of a patient with EGFR-mutant lung cancer harboring de novo MET amplification: Successful treatment with gefitinib and crizotinib. (March 2019) - Zheng, Xuanxuan; Zhang, Guowei; Li, Peng; Zhang, Mina; Yan, Xiangtao; Zhang, Xiaojuan; Yang, Jinbo; Li, Haixia; Liu, Xiyang; Ma, Zhiyong; Wang, Huijuan
Highlights: De novo MET amplification is believed to promote primary resistance to EGFR tyrosine kinase inhibitors in the non-small cell lung cancer. Treatment of patients with EGFR mutant and de novo MET amplification is unknown. We report the progress free survival of the patient harboring the rare mutations for the first time. The combination of EGFR- and MET- tyrosine kinase inhibitors may be an effective treatment for the rare mutations. Abstract: Objective: De novo mesenchymal-epithelial transition (MET) amplification is believed to promote primary resistance to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors in the non-squamous non-small cell lung cancer (NSCLC). We sought to seek the treatment of a patient with EGFR-mutant NSCLC harboring de novo MET amplification. Materials and methods: After clinical diagnosis, tissue and plasma samples were obtained from the patient and subjected to next-generation sequencing to identify and dynamic monitor the mutations. Results: The patient was treated with gefitinib monotherapy in the beginning and experienced primary resistance to gefitinib but achieved a good response to the combination therapy of gefitinib and crizotinib. He achieved a 16.8-month progress free survival with the combination therapy. NGS of plasma circulating cell-free tumor DNA shown that L858R mutation was no longer detectable and the copy number of MET dropped when the patient got remission. Conclusions: The combination of EGFR- and MET- tyrosine kinase inhibitors may be an effective treatment for the rare mutations.